Integrated Thematic Learning Design Based on the School Environment to Develop Students' Creative and Critical Thinking - Mawardi; Hardini, Agustina Tyas Asri (Jurnal Penelitian dan Pengembangan Pendidikan, 2024)
This research aims to improve teachers' abilities in designing their learning so that it will have an impact on the growth of students' critical and creative thinking abilities. To achieve this goal it is used research type Research and Development (R&D) which consists of a preliminary study; model design and development; and model testing. Data was collected through interviews, literature studies and small-scale surveys. This research involved 4 teachers and 102 elementary school students. The instruments used include questionnaires and test questions. Data analysis techniques use percentage and categorical descriptive analysis. Results The main research shows that implementing this design can effectively develop students' creative and critical thinking abilities. Through a thematic approach that integrates various subjects by utilizing the school environment as a learning resource, students are more actively involved in the learning process. The implications of this research show that applying a contextual learning approach can be an effective strategy in education to develop students' critical and creative thinking abilities.